2018
DOI: 10.1016/j.annepidem.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality patterns during 1918–1921 influenza pandemic in the state of Arizona, USA

Abstract: The 1918-1921 influenza pandemic killed an estimated 0.8% of the Arizona population in three closely spaced consecutive waves. The mortality impact of the fall 1918 wave in Arizona lies in the upper range of previous estimates reported for other US settings and Europe, with a telltale age distribution of deaths concentrated among young adults. We identified a significant rise in tuberculosis-related mortality during the pandemic, lending support to the hypothesis that tuberculosis was a risk factor for severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 32 publications
0
45
0
Order By: Relevance
“…We also found evidence of a powerful recrudescent wave after the enduring second wave; the recrudescent wave peaked at the very end of 1919 and appeared throughout the world in the spring of 1920 ( 1 , 3 , 9 , 17 , 19 21 , 24 , 37 , 44 ). In Madrid, all-cause excess rates were on par with those of the elongated second wave, and all-cause and respiratory-related excess mortality rates were higher than in the spring 1918 wave.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…We also found evidence of a powerful recrudescent wave after the enduring second wave; the recrudescent wave peaked at the very end of 1919 and appeared throughout the world in the spring of 1920 ( 1 , 3 , 9 , 17 , 19 21 , 24 , 37 , 44 ). In Madrid, all-cause excess rates were on par with those of the elongated second wave, and all-cause and respiratory-related excess mortality rates were higher than in the spring 1918 wave.…”
Section: Discussionmentioning
confidence: 63%
“…In Madrid, all-cause excess rates were on par with those of the elongated second wave, and all-cause and respiratory-related excess mortality rates were higher than in the spring 1918 wave. In other countries and cities where this wave has been documented, a slight shift in the age-specific mortality often occurred, with a return to high excess mortality among people older than 65 years ( 9 , 17 , 19 , 21 , 24 ). As in our study, the death rate of young adults reported in these locations often dropped slightly but remained persistently high and well above the prepandemic level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…City in February 1918 [1] and in Kentucky [5], Arizona [9], Missouri [10] and military training camps throughout the country in March-April 1918 [32]. Influenza incidence increased in Figure 4B).…”
Section: In the Us Such Epidemiological Evidence Supports Pandemic Amentioning
confidence: 97%
“…Such data originated from nearly forgotten mortality and morbidity reports available from surveillance systems established in the US and Europe 100 years ago (see for example [1][2][3][4][5]) and from labor-intensive compilation of church records, grave yards, and individual death certificates (e.g. [5][6][7][8][9][10]).…”
Section: Introductionmentioning
confidence: 99%